Relationship Between Street Skateboards and Pedestrians in The City of Bandung - Yazid Nuur Shafwan (Cinematology: Journal Anthology of Film and Television Studies, 2023)
The development of skateboarding in Indonesia can be felt in several cities, one of which is the city of Bandung, the city of Bandung is one of the cities that has creative potential. There are so many enthusiasts who are enthusiastic about this skateboarding sport. The rise of skateboarders who use sidewalks as a playground has disrupted general comfort. The purpose of this study is to determine the relationship between street skateboards and pedestrians in the city of Bandung, the research was carried out through direct distribution of questionnaires and through social media in the form of google form, the population used was an infinite population with 349 samples and a 5% margin of error aimed at the community. especially for pedestrians and skateboarders, the statistical test used is the Chi-Square statistical test and results in a relationship between street skateboarding and pedestrians in the city of Bandung.